Studi Evaluasi Profesionalisme Amil Zakat Tradisonal - Saiful Bahri (LPPM ISNJ Bengkalis, 2015)
There are numbers of professionalism results such as an aspect of recruitment, compensation, competence, and independence of entity who manages zakat asset. As basically study, understanding to Islam as in-depth theory manifested to their technical skill, what we call by amil.